If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7y = 11 Solving 3x + 7y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 3x + 7y + -7y = 11 + -7y Combine like terms: 7y + -7y = 0 3x + 0 = 11 + -7y 3x = 11 + -7y Divide each side by '3'. x = 3.666666667 + -2.333333333y Simplifying x = 3.666666667 + -2.333333333y
| b^3=25b | | 3x+49=7x+13 | | (n-4)*7=70 | | 6x-3=14x-91 | | y=4x+5 | | (n-3)*2=6 | | 5d+4=39 | | (n+1)*4=8 | | (4-8+3)-(9+6-5)= | | n-15=14 | | n-12=20 | | 5w-7+7(w-3)-4(w-9)= | | 3t^2-10t-8=0 | | 2c-1=9 | | n-4=16 | | n*4=12 | | X-8.9=8.9 | | n+32=47 | | 3b=27 | | n+14=21 | | 2(t+5)+13= | | a^2-2ab+2b^2-4b^3=0 | | y^2-16x+2y+49=0 | | 6x-4=13x-46 | | n-3=15 | | n+25=42 | | 35-2x+6-18x=14-30x+32 | | 2x^2-12x-y+14=0 | | 2(x-1)+4(5-x)+x=(x-18) | | 2a(a-5)+4(a-5)= | | 6x^2+53x-9=0 | | y-16=38 |